Food insecurity and weight loss during wartime: a mixed-design study from the Gaza Strip - Asem Alnabih; Nour-Alhuda Alnabeh; Yousef Aljeesh; Belal Aldabbour (Journal of Health, Population and Nutrition)
Abstract Background Food insecurity is an important aspect of human suffering during wartime. Besides its ferocity, the Gaza conflict of 2023–2024 has been marked by severe food and medication shortages that exacerbated the human toll and worsened the suffering of the population. Methods A cross-sectional, mixed methods study that in April 2024 collected quantitative and qualitative data to assess food insecurity and malnutrition among residents of the Northern part of the Gaza Strip during the first seven months of the war. Quantitative data assessed weight loss among participants as a marker of starvation. Qualitative interviews evaluated food availability, food variability, and changing eating habits. Demographics were represented as counts and percentages. Weight was reported as mean ± SD. The Spearman Correlation Coefficient evaluated potential correlations of weight loss with sex, place of residence, and age. Statistical significance was set at a p-value less than 0.05. Results 497 participants were recruited, including 330 males (66.4%) and 167 females (33.6%). The age range was (13–83 years). The mean baseline weight was 84.94 kg ± 20.06, with a weight range (35–180 kg). In April 2024, the mean weight had dropped to 66.22 kg ± 14.34, representing an average decline of 18.72 kg (new weight range 28–142 kg). Age was associated with a weak positive correlation with weight loss (r = .204, p = .000). Qualitative interviews with 95 breadwinners or homemakers revealed a high prevalence of hunger and severe shortages in food quantity, quality, and variability. Physical and financial barriers significantly impacted food sourcing. Also, due to food shortages, most participants reported high consumption of edible wild plants and unconventional types of flour such as corn flour or grounded animal feed. Conclusions The study demonstrated high levels of weight loss and marked food insecurity in the Northern Gaza Strip during the conflict. The quantitative and qualitative food shortages outlined in this study present a risk for a host of potentially serious and irreversible future complications.